Intensive measurements of gas, water, and energy exchange between vegetation and troposphere during the MONTES Campaign in a vegetation gradient from short semi-desertic shrublands to tall wet temperate forests in the NW Mediterranean basin - Penuelas, J; Guenther, A; Rapparini, F; Llusia, J; Filella, I; Seco, R; Estiarte, M; Mejia-Chang, M; Ogaya, R; Ibáñez, J; Sardans, J; Castaño, L M; et al. (Atmospheric Environment)
Abstract MONTES (“Woodlands”) was a multidisciplinary international field campaign aimed at measuring energy, water and especially gas exchange between vegetation and atmosphere in a gradient from short semi-desertic shrublands to tall wet temperate forests in NE Spain in the North Western Mediterranean Basin (WMB). The measurements were performed at a semidesertic area (Monegros), at a coastal Meditrerranean shrubland area (Garraf), at a typical Mediterranean holm oak forest area (Prades) and at a wet temperate beech forest (Montseny) during spring (April 2010) under optimal plant physiological conditions in driest-warmest sites and during summer (July 2010) with drought and heat stresses in the driest-warmest sites and optimal conditions in the wettest-coolest site. The objective of this campaign was to study the differences in gas, water and energy exchange occurring at different vegetation coverages and biomasses. Particular attention was devoted to quantitatively understand the exchange of biogenic volatile organic compounds (BVOCs) because of their biological and environmental effects in the WMB. A wide range of instruments (GC-MS, PTR-MS, meteorological sensors, O3 monitors,…) and vertical platforms such as masts, tethered balloons and aircraft were used to characterize the gas, water and energy exchange at increasing footprint areas by measuring vertical profiles. In this paper we provide an overview of the MONTES campaign: the objectives, the characterization of the biomass and gas, water and energy exchange in the 4 sites-areas using satellite data, the estimation of isoprene and monoterpene emissions using MEGAN model, the measurements performed and the first results. The isoprene and monoterpene emission rates estimated with MEGAN and emission factors measured at the foliar level for the dominant species ranged from about 0 to 0.2 mg m-2 h-1 in April. The warmer temperature in July resulted in higher model estimates from about 0 to ca 1.6 mg m-2 h-1 for isoprene and ca. 4.5 mg m-2 h-1 for monoterpenes, depending on the site vegetation and footprint area considered. There were clear daily and seasonal patterns with higher emission rates and mixing ratios at midday and summer relative to early morning and early spring. There was a significant trend in CO2 fixation (from 1 to 10 mg C m-2 d-1), transpiration (from x 1 to 5 kg C m-2 d-1), and sensible and latent heat from the warmest-driest to the coolest-wettest site. The results showed the strong land-cover-specific influence on emissions of BVOCs, gas, energy and water exchange, and therefore demonstrate the potential for feed-back to atmospheric chemistry and climate.
Keywords: aircraft; Boundary Layer; CH4; CO2; Evapotranspiration; green biomass; isoprene; lai; Land Cover; latent heat; masts; MEGAN; Monoterpenes; N2O; NDVI; O3; sensible heat; tethered balloons; Vegetation; vertical profiles; VOCs

MONITORING TOOLS TO ASSESS VEGETATION SUCCESSIONAL REGRESSION AND PREDICT CATASTROPHIC SHIFTS AND DESERTIFICATION IN MEDITERRANEAN RANGELAND ECOSYSTEMS - ALADOS, C L; ELAICH, A; PAPANASTASIS, V P; OZBEK, H; Freitas, H (Desertification in the Mediterranean Region a Security Issue)
The relationship between grazing intensity and ecosystem performance is complex and can depend on the prevailing ecological conditions. Previous studies have revealed that, in traditional grazing ecosystems, grazing can reduce ecosystem diversity in poor soils, but increase diversity and productivity in rich ecosystems subject to moderate grazing pressure. We are interested in detecting long-term structural changes or drift in an ecosystem before it is too late to prevent irreversible degradation. We analyzed vegetation spatial patterns and complexities of four Mediterranean communities: Tihmadit Region (Middle Atlas, Morocco), Camiyayla (Namrum) Region (Taurus Mountain, Turkey), Sykia Region (south of the Sithonia Peninsula, Greece), and Cabo de Gata Nijar Natural Park, Spain. Grazing disturbance was most intense near shelter and water points, which lead to gradients in soil surface disruption, compaction, and changes in the composition and cover of perennial vegetation. Dense matorral was more resistant to species loss than were moderately dense and scattered matorral, and grassland. Information fractal dimension decreased as we moved from a dense matorral to a discontinuous matorral, and increased as we moved to a more scattered matorral and to a grassland, which resulted in two opposing processes (interaction declining with ecosystem development, and immigration increasing with degradation) in a common pattern, i.e., small patches homogeneously distributed in the landscape. Characteristic species of the natural vegetation declined in frequency and organization in response to higher grazing disturbance, while species of disturbed areas exhibited the opposite trend. Overall, the spatial organization of the characteristic plants of each community decreased with increasing vegetation degradation, with the intensity of the trend being related to the species’ sensitivity to grazing. Developmental instability analyses of key species were used to determine the sensitivity of dominant key species to grazing pressure. Palatable species, which are better adapted to being eaten, such as Periploca laevigata, Phillyrea latifolia and Genista pseudopilosa, were able to resist moderate grazing pressure, while species of disturbed, grazed sites did not change developmental instability in response to increasing grazing pressure, such as Thymus hyemalis, Teucrium lusitanicum and Cistus monspeliensis. The usefulness of these monitoring tools in preventing land degradation is discussed.
Keywords: disturbance; grassland; Grazing; matorral (voyant); Mediterranean ecosystems; Spatial pattern; Vegetation

Drought stress does not protect Quercus ilex L. from ozone effects: results from a comparative study of two subspecies differing in ozone sensitivity - Alonso, R; Elvira, S; González-Fernández, I; Calvete, H; García-Gómez, H; Bermejo, V (Plant Biology, 2014)
Long-term effects of ozone (O3) exposure and drought stress were assessed on two subspecies of Quercus ilex: ssp. ilex and ssp. ballota. Two-year-old seedlings were continuously exposed for 26 months in open-top chambers to three O3 treatments: charcoal filtered air, non-filtered air and non-filtered air supplemented with 40 nl·l−1 O3. Additionally, two irrigation regimes were adopted: half of the plants were well-watered and the others received half of the water supplied to control plants. Growth, shoot water potential and gas exchange rates were assessed seasonally, and biomass accumulation was determined at the end of the experiment. Drought stress caused higher reductions of gas exchange, growth and biomass accumulation than O3 exposure in both subspecies. The combination of O3 and drought stress caused further decreases of accumulated aboveground biomass but no additive effects were observed on gas exchange rates or root biomass. Thus, drought stress did not protect Q. ilex from O3 effects on biomass when the response of the whole plant was considered. Q. ilex ssp. ballota was more sensitive to O3 and ssp. ilex was more affected by drought stress. The different O3 sensitivity was not only related to pollutant uptake but also to the ability of plants for resource acquisition and allocation. Based on biomass dose–response functions, Q. ilex is more resistant to O3 than other European evergreen tree species, however, O3 represents an additional stress factor that might be impairing plant ability to withstand current and future climate change.
Keywords: evergreen broadleaf mediterranean; Evergreen broadleaf Mediterranean vegetation; Gas exchange; Growth; Holm oak; ozone response functions; Vegetation

The Late Holocene in the western Pyrenees: A critical review of the current situation of palaeopalynological research - Hernández-Beloqui, Begoña; Iriarte-Chiapusso, María-José; Echazarreta-Gallego, Amaya; Ayerdi, Miren (Quaternary International, 2014)
As the vegetation is a social product resulting from the interaction of human beings with the environment, its study contributes towards an understanding of past human cultures. In particular, during the Late Holocene, the socio-cultural evolution of humans has undergone a series of major changes, which have impacted on their environmental setting. In this way, palynological analysis has been able to observe an interesting evolution in anthropization processes since the early Iron Age. However, these observations are conditioned by the volume of deposits that have been studied and their chrono-cultural sequencing. Other factors, such as the deficient preservation of sporo-pollen remains and the lack of well-dated continuous records in non-anthropic deposits, equally restrict our knowledge of the topic. The information available to date confirms that since the first millennium cal BC the vegetation (determining the bio-geographic variety of the territory) has been greatly influenced by human action, on both the Atlantic and the Mediterranean sides of the watershed.
Keywords: Anthropization; Late Holocene; Northern Iberian Peninsula; Palaeopalynology; Vegetation

Predicting the natural vegetation in a region by comparing the pollen in two biological vectors: bryophytes and honey - González-Porto, A V; Martín-Arroyo, T (Grana, 2013)
The range of pollen that can be found around the city of Sigüenza has been analysed (La Alcarria, north-eastern region, Guadalajara, Spain), an area currently included in the territory comprising the Protected Origin Denomination ‘Miel de la Alcarria’. We studied the pollen recovered from two different types of biological sensors: bryophytes, live material used to study the recent pollen rain, and honey. The aim of this study was to try to establish the relationship between the pollen collected from both types of sensors and the existing natural vegetation in the area using comparative statistical methods. More than 7500 pollen grains were observed from the bryophyte samples and included 35 pollen types. Conversely, the pollen present in 37 honey samples contained 46 pollen types with a total of 46 000 pollen grains counted. The data presented in this study proves the relationship between the bryophyte pollen spectrum and the local vegetation present in a geographical area. However, it indicates that the pollen content in honey is a more effective measurement to determine spatial distribution of the plant species.We conclude that the pollen present in honey may better predict the vegetation in a region than that recovered from bryophytes.
Keywords: Apis mellifera; bryophytes layer; Guadalajara; iberian peninsula; landscape plant; surface pollen sample; Vegetation

Late postglacial paleoenvironmental change in the northeastern Mediterranean region: Combined palynological and molecular biomarker evidence - Kouli, K.; Gogou, A.; Bouloubassi, I.; Triantaphyllou, M. V.; Ioakim, Chr; Katsouras, G.; Roussakis, G.; Lykousis, V. (Quaternary International, 2012)
Three gravity cores collected from the NE Mediterranean (NEMR) across a transect from the northern Aegean Sea (North Skyros basin) to the south Cretan margin (SCM), were investigated for pollen and terrestrial biomarkers derived from epicuticular waxes of vascular plants during the last w20 ky. Pollen data show diversiﬁed mixed temperate forest in the northern borderlands and enhanced Mediterranean vegetation in the southern areas, documenting an NeS climatic trend. Terrestrial plant biomarkers and their diagnostic geochemical indices exhibit latitudinal patterns which are interpreted in terms of the different delivery pathways (ﬂuvial/runoff vs. atmospheric transport), resulting from the climate conditions during different periods. During the Late Glacial and early deglaciation periods (20e14 ka BP) relatively increased humidity (H-index) is recorded in the north Aegean Sea, while in the South drier climate was the limiting factor for vegetation development. During this interval, terrestrial n-alkanes showed increased accumulation rates, suggesting massive transport of terrestrial organic matter through runoffs and rivers, followed by weaker input after 14 ka BP. After w11 ka BP a major expansion of forest cover is evidenced in the NEMR, accompanied by a higher H-index because of the climatic amelioration. The forest vegetation exhibited regionally different characteristics, with cool temperate taxa being more abundant in the Aegean cores, while the SCM record is being featured by Mediterranean elements. At the onset of the Holocene and throughout the Holocene Climatic Optimum the delivery of terrestrial biomarkers increased and became more signiﬁcant in the Aegean sites compared to the SCM site. Within the Holocene, the average chain length (ACL) of long chain n-alkanes exhibits lower values in the northern Aegean than in the southeastern Aegean and SCM, indicating the predominance of warmer species southwards. Finally, the H-index records a conspicuous humidity increase between 5.4 and 4.3 ka BP in the south Aegean that coincides with an increase in the terrestrial biomarker supply and the deposition of a distinct sapropel-like layer, SMH (Sapropel Mid Holocene). Similar trends in T (temperature) and H indices are slightly delayed and attenuated in the northern Aegean and are accompanied by an increase in the ACL index. A noticeable increase in the accumulation rates (ARs) of terrestrial biomarkers and the HPA index values during this period are clearly recorded in all three cores, indicative of enhanced terrigenous inputs of organic matter along with higher in-situ preservation.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Aegean Sea; climatic variability (voyant); Holocene; Mediterranean; pollen; terrestrial biomarkers; Vegetation

Nitrogen dioxide (NO2) uptake by vegetation controlled by atmospheric concentrations and plant stomatal aperture - Chaparro-Suarez, I. G.; Meixner, F. X.; Kesselmeier, J. (Atmospheric Environment, 2011)
Nitrogen dioxide (NO2) exchange between the atmosphere and ﬁve European tree species was investigated in the laboratory using a dynamic branch enclosure system (consisting of two cuvettes) and a highly speciﬁc NO2 analyzer. NO2 measurements were performed with a sensitive gas phase chemiluminescence NO detector combined with a NO2 speciﬁc (photolytic) converter, both from Eco-Physics (Switzerland). This highly speciﬁc detection system excluded bias from other nitrogen compounds. Investigations were performed at two light intensities (Photosynthetic Active Radiation, PAR, 450 and 900 mmol m2 s 1 ) and NO2 concentrations between 0 and 5 ppb. Ambient parameters (air temperature and relative humidity) were held constant. The data showed dominant NO2 uptake by the respective tree species under all conditions. The results did not conﬁrm the existence of a compensation point within a 95% conﬁdence level, though we cannot completely exclude emission of NO2 under very low atmospheric concentrations. Induced stomatal stricture, or total closure, by changing light conditions, as well as by application of the plant hormone ABA (Abscisic Acid) caused a corresponding decrease of NO2 uptake. No loss of NO2 to plant surfaces was observed under stomatal closure and species dependent differences in uptake rates could be clearly related to stomatal behavior
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Deposition; Gas exchange; Nitrogen dioxide; Stomatal uptake; Vegetation

Remote estimation of carbon dioxide uptake by a Mediterranean forest - GARBULSKY, MARTÍN F; Penuelas, Josep; Papale, Dario; Filella, Iolanda (Global Change Biology, 2008)
The estimation of the carbon balance in ecosystems, regions, and the biosphere is currently one of the main concerns in the study of the ecology of global change. Current remote sensing methodologies for estimating gross primary productivity are not satisfactory because they rely too heavily on (i) the availability of climatic data, (ii) the definition of land-use cover, and (iii) the assumptions of the effects of these two factors on the radiation-use efficiency of vegetation (RUE). A new methodology is urgently needed that will actually assess RUE and overcome the problems associated with the capture of fluctuations in carbon absorption in space and over time. Remote sensing techniques such as the widely used reflectance vegetation indices (e.g. NDVI, EVI) allow green plant biomass and therefore plant photosynthetic capacity to be assessed. However, there are vegetation types, such as the Mediterranean forests, with a very low seasonality of these vegetation indices and a high seasonality of carbon uptake. In these cases it is important to detect how much of this capacity is actually realized, which is a much more challenging goal. The photochemical reflectance index (PRI) derived from freely available satellite information (MODIS sensor) presented for a 5-year analysis for a Mediterranean forest a positive relationship with the RUE. Thus, we show that it is possible to estimate RUE and GPP in real time and therefore actual carbon uptake of Mediterranean forests at ecosystem level using the PRI. This conceptual and technological advancement would avoid the need to rely on the sometimes unreliable maximum RUE.
Keywords: carbon cycle; CO2 uptake; eddy covariance; Mediterranean forests; MODIS; primary productivity; radiation use efficiency; Remote sensing; Vegetation

Remote estimation of carbon dioxide uptake by a Mediterranean forest - Garbulsky, Martín F.; Penuelas, Josep; Papale, Dario; Filella, Iolanda (Global Change Biology, 2008)
The estimation of the carbon balance in ecosystems, regions, and the biosphere is currently one of the main concerns in the study of the ecology of global change. Current remote sensing methodologies for estimating gross primary productivity are not satisfactory because they rely too heavily on (i) the availability of climatic data, (ii) the definition of land-use cover, and (iii) the assumptions of the effects of these two factors on the radiation-use efficiency of vegetation (RUE). A new methodology is urgently needed that will actually assess RUE and overcome the problems associated with the capture of fluctuations in carbon absorption in space and over time. Remote sensing techniques such as the widely used reflectance vegetation indices (e.g. NDVI, EVI) allow green plant biomass and therefore plant photosynthetic capacity to be assessed. However, there are vegetation types, such as the Mediterranean forests, with a very low seasonality of these vegetation indices and a high seasonality of carbon uptake. In these cases it is important to detect how much of this capacity is actually realized, which is a much more challenging goal. The photochemical reflectance index (PRI) derived from freely available satellite information (MODIS sensor) presented for a 5-year analysis for a Mediterranean forest a positive relationship with the RUE. Thus, we show that it is possible to estimate RUE and GPP in real time and therefore actual carbon uptake of Mediterranean forests at ecosystem level using the PRI. This conceptual and technological advancement would avoid the need to rely on the sometimes unreliable maximum RUE.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: carbon cycle; CO2 uptake; eddy covariance; Mediterranean forests; MODIS; primary productivity; radiation use efficiency; Remote sensing; Vegetation

Parent material effects on Mediterranean woodland ecosystems in NE Spain - Kooijman, A M; Jongejans, J; Sevink, J (Catena, 2005)
A field survey of an evergreen Mediterranean woodland area in NE Spain on three silica-rich parent materials (granite, granodiorite and schist) was used to test whether parent material had a separate effect on ecosystem functioning in addition to aspect and position on the slope. As expected, vegetation was taller and denser on north-facing slopes and/or lower slope positions. However, parent material appeared to have additional effects, with significant increases in tree height, tree cover, shrub height and ratio of woodland to maquis vegetation from granite towards granodiorite and schist. There was also a parallel increase in mull humus forms, indicating increasing litter breakdown. The lower productivity on granite may be partly attributed to drought stress, as indicated by the greater proportion of shallow soils and the sandy to loamy sand texture. However, nutrient stress may be equally important. Plant N/P ratios were significantly greater on granite, and plant and soil P contents were less than on the other parent materials, suggesting that P-availability was limited on granite. The greater productivity of soils on schist than on granodiorite may reflect less severe drought stress because of their finer texture. These results suggest that parent material is an important factor regulating productivity in Mediterranean ecosystems through varying drought stress and availability of nutrients.
Keywords: biomass; Drought stress; nitrogen; Nutrient; phosphorus; Soil; Vegetation; water

Climatic factors and establishment of Quercus ilex-communities in Trieste Province (NE Italy) - Codogno, M.; Furlanetto, A. (Annali di Botanica, 2004)
In the coastal area called "Cernizza" (near Duino. ca 15 km NW from Trieste), at an altitude between 0 and 40 m. is located a wood vegetation complex characterized by Quercus ilex and Carpinus orientalis. The bedrocks of this site is carbonatic. This wood vegetation does not occur in other sites or the Trieste province, where deciduous oak woods (Q. pubescells, Q. petraea s.1.) are dominant both on arenaceus and on carbonatic rocks. Other Quercus ilex communities are occurring only as scrubs on the calcareous coastal cliffs characterized by primitive lithosoils. In order to detect if this wood community might be an expression of the c1imate dominating this particular zone, some Duino's c1imatic data, relative lo a record period of 9 years. have been compared with the Trieste's ones. The analysed parameters were the following: air temperature. rainfall, evaporation. wind speed and relative humidity. From the comparison of these paramenters it emerged that the Duino's climate is more humid than the Trieste's one. Only in springtime Duino is less rainy than Trieste according lo the analysis of the monthly mean values of precipitation. From the ecophysiological point of view, a study of the seasonal changes of the root hydraulic conductance in some forest trees (Nardini el al .. 1998) has pointed out the superiority of Quercus ilex compared to Quercus pubescens, as regards the competitive ability of the seedlings during the spring. For this reason, the smaller spring rainfall could explain the occurrence of Quercus ilex stands not only in the neighbourhood of Duino but also at the beginning of the large valleys characterized by S•N direction in the South Eastern Alps.
Keywords: climate; Holm oak; plant ecology; Quercus ilex; Trieste province; Vegetation

Climatic factors and establishment of Quercus ilex-communities in Trieste Province (NE Italy) - Codogno, M; Furlanetto, A (Annali di Botanica, 2004)
In the coastal area called "Cernizza" (near Duino. ca 15 km NW from Trieste), at an altitude between 0 and 40 m. is located a wood vegetation complex characterized by Quercus ilex and Carpinus orientalis. The bedrocks of this site is carbonatic. This wood vegetation does not occur in other sites or the Trieste province, where deciduous oak woods (Q. pubescells, Q. petraea s.1.) are dominant both on arenaceus and on carbonatic rocks. Other Quercus ilex communities are occurring only as scrubs on the calcareous coastal cliffs characterized by primitive lithosoils. In order to detect if this wood community might be an expression of the c1imate dominating this particular zone, some Duino's c1imatic data, relative lo a record period of 9 years. have been compared with the Trieste's ones. The analysed parameters were the following: air temperature. rainfall, evaporation. wind speed and relative humidity. From the comparison of these paramenters it emerged that the Duino's climate is more humid than the Trieste's one. Only in springtime Duino is less rainy than Trieste according lo the analysis of the monthly mean values of precipitation. From the ecophysiological point of view, a study of the seasonal changes of the root hydraulic conductance in some forest trees (Nardini el al .. 1998) has pointed out the superiority of Quercus ilex compared to Quercus pubescens, as regards the competitive ability of the seedlings during the spring. For this reason, the smaller spring rainfall could explain the occurrence of Quercus ilex stands not only in the neighbourhood of Duino but also at the beginning of the large valleys characterized by S•N direction in the South Eastern Alps.
Keywords: climate; Holm oak; plant ecology; Quercus ilex; Trieste province; Vegetation

Metropolitan area of Rome: an integrated vegetation study by remote sensing and field data - Giannini, M.; Anselmi, S.; Melini, S.; Allegrini, A.; Manes, F. (Remote Sensing and Data Fusion over Urban Areas, IEEE/ISPRS Joint Workshop 2001, 2001)
The objective of this work is to assess the impact of environmental stresses, both natural (water stress, due to summer dryness typical of the Mediterranean climate) and anthropogenic (atmospheric pollution), on the vegetation in sites of great naturalistic value and under strong anthropic pressure in the Rome metropolitan area. The species <e1>Q</e1>uercus ilex L<e1>.</e1> (holm oak), an evergreen oak, has been studied through ecophysiological measurements performed in the field and Landsat TM images relating to the Rome metropolitan area. The results obtained show a greater degree of structural and functional alteration in individual holm oaks within the urban area compared with those in the protected areas outside of the central zone. In particular, in 1993 the main stress factor for vegetation is attributable to climatic conditions, whereas in 1998 ozone atmospheric concentration caused an evident alteration of the parameters studied
The following values have no corresponding Zotero field: periodical: Remote Sensing and Data Fusion over Urban Areas, IEEE/ISPRS Joint Workshop 2001
Keywords: Environmental stresses; metropolitan area; multiscale approach; Vegetation

Metropolitan area of Rome: an integrated vegetation study by remote sensing and field data - Giannini, M; Anselmi, S; Melini, S; Allegrini, A; Manes, F (Remote Sensing and Data Fusion over Urban Areas, IEEE/ISPRS Joint Workshop 2001, 2001)
The objective of this work is to assess the impact of environmental stresses, both natural (water stress, due to summer dryness typical of the Mediterranean climate) and anthropogenic (atmospheric pollution), on the vegetation in sites of great naturalistic value and under strong anthropic pressure in the Rome metropolitan area. The species <e1>Q</e1>uercus ilex L<e1>.</e1> (holm oak), an evergreen oak, has been studied through ecophysiological measurements performed in the field and Landsat TM images relating to the Rome metropolitan area. The results obtained show a greater degree of structural and functional alteration in individual holm oaks within the urban area compared with those in the protected areas outside of the central zone. In particular, in 1993 the main stress factor for vegetation is attributable to climatic conditions, whereas in 1998 ozone atmospheric concentration caused an evident alteration of the parameters studied
Keywords: Environmental stresses; metropolitan area; multiscale approach; Vegetation

Datos sobre la flora y vegetación del Parque Natural de los Alcornocales (Cádiz-Málaga, España) - Pérez Latorre, A V (Acta botánica malacitana, 1999)
We have carried out a study about the flora, vegetation and landscape inthe Natural Park Los Alcornocales, located in the provinces of Cádiz and Málaga (SW of the Iberian Peninsula, Andalusia). The maximum altitude in the Park is 1091 m.; the dominant litology is characterised by sandstones and clays, in the NW prevail the limestones. The annual rainfalls are very abundant (between 800 and 1400 mm.) as well as the fogs regime, caused by the nearness to the Strait of Gibraltar; we have recognized two bioclimactic belts, thermo (annual mean temperature 17-18°C) and mesomediterranean (14-16°C) with accused oceanity. As a result, more than 1300 taxa of vascular plants have been catalogued, emphasizing in this work 77, because they are protected species, endemics or first records for western Andalusia; among them, 9 species are relictic ferns and have a great phytogeographic value. A total of 89 associations and communities have been inventoried. We have accomplished commentaries on sintaxa with a range superior to association. We lectotypified a subassociation and one association is neotypified. We describe as new sintaxa one order (Rhododendro pontici-Prunetalia lusitanicae), two alliances ldodendro ponticiPrunion lusitanicae and Salicion pedicellatae), 6 associations, 8 subassociations ad 1 combination. We have recognized 6 climactic series, among them one is new and characterised by forests of Quercus:broteroi on calcareous soils (Oleo sylvestris-Querceto broteroi S), other two are forests of Quercus suber on sandstones, another one is characterised by Quercus canariensis in wet slopes, one of Quercus pyrenaica in the summits and one of Quercus rotundifolia on lowland calcareous soils. As a mixed serie bound to the conditions of the vertisols occurs forests ofOlea sylvestris. As permanent vegetation on calcareous solis appears Ceratonia siliqua; on sandstones appears Junipertts oxycedrus; in summits flogged by strong winds we recognize a community with Quercus lusitanica and on rocky sandstones a relictual variant with Pinus pinaster. A mixed serie bound to the environmental humidity conditions as well as to wet soils is characterized by Rhododendron ponticum, similar to the macaronesian laurisilva. The series linked to rivers in the Park are characterised by: Alnus glutinosa (permanent stream rivers on sandstones), Salix pedicellata (partially droughted rivers), Populus alba (fluvisols), Fraxinus angustifolia (riverine sandyargilic soils), Nerium oleander (totally droughted rivers), Tarnarix africana (erratic or halophyll streams) and wet heaths with Erica ciliaris. Also exist communities mosaics bound to ecological corridors, human environments, rocks and cliffs, epiphytes, acrohalophylls and those tipycal of saline and aquatic environments. Finally, a commented syntaxonomic scheme, some inventories tables corresponding to the new or commented syntaxa and a map of the vegetation series of the Park are presented
Keywords: Andalucía; España; Flora; Los Alcornocales; Natural Park; sintaxonomy; Vegetation

Datos sobre la flora y vegetación del Parque Natural de los Alcornocales (Cádiz-Málaga, España) - Pérez Latorre, A. V. (Acta botánica malacitana, 1999)
We have carried out a study about the flora, vegetation and landscape inthe Natural Park Los Alcornocales, located in the provinces of Cádiz and Málaga (SW of the Iberian Peninsula, Andalusia). The maximum altitude in the Park is 1091 m.; the dominant litology is characterised by sandstones and clays, in the NW prevail the limestones. The annual rainfalls are very abundant (between 800 and 1400 mm.) as well as the fogs regime, caused by the nearness to the Strait of Gibraltar; we have recognized two bioclimactic belts, thermo (annual mean temperature 17-18°C) and mesomediterranean (14-16°C) with accused oceanity. As a result, more than 1300 taxa of vascular plants have been catalogued, emphasizing in this work 77, because they are protected species, endemics or first records for western Andalusia; among them, 9 species are relictic ferns and have a great phytogeographic value. A total of 89 associations and communities have been inventoried. We have accomplished commentaries on sintaxa with a range superior to association. We lectotypified a subassociation and one association is neotypified. We describe as new sintaxa one order (Rhododendro pontici-Prunetalia lusitanicae), two alliances ldodendro ponticiPrunion lusitanicae and Salicion pedicellatae), 6 associations, 8 subassociations ad 1 combination. We have recognized 6 climactic series, among them one is new and characterised by forests of Quercus:broteroi on calcareous soils (Oleo sylvestris-Querceto broteroi S), other two are forests of Quercus suber on sandstones, another one is characterised by Quercus canariensis in wet slopes, one of Quercus pyrenaica in the summits and one of Quercus rotundifolia on lowland calcareous soils. As a mixed serie bound to the conditions of the vertisols occurs forests ofOlea sylvestris. As permanent vegetation on calcareous solis appears Ceratonia siliqua; on sandstones appears Junipertts oxycedrus; in summits flogged by strong winds we recognize a community with Quercus lusitanica and on rocky sandstones a relictual variant with Pinus pinaster. A mixed serie bound to the environmental humidity conditions as well as to wet soils is characterized by Rhododendron ponticum, similar to the macaronesian laurisilva. The series linked to rivers in the Park are characterised by: Alnus glutinosa (permanent stream rivers on sandstones), Salix pedicellata (partially droughted rivers), Populus alba (fluvisols), Fraxinus angustifolia (riverine sandyargilic soils), Nerium oleander (totally droughted rivers), Tarnarix africana (erratic or halophyll streams) and wet heaths with Erica ciliaris. Also exist communities mosaics bound to ecological corridors, human environments, rocks and cliffs, epiphytes, acrohalophylls and those tipycal of saline and aquatic environments. Finally, a commented syntaxonomic scheme, some inventories tables corresponding to the new or commented syntaxa and a map of the vegetation series of the Park are presented
Keywords: Andalucía; España; Flora; Los Alcornocales; Natural Park; sintaxonomy; Vegetation

Datos sobre la flora y vegetación de la Serranía de Ronda (Málaga, España) - Pérez Latorre, A V; Navas, P; Navas, D; Gil, Yolanda; Cabezudo, Baltasar (Acta Botanica Malacitana, 1998)
New data on flora and vegetation in the Serranía de Ronda (Málaga, Andalusia, Spain). A floristic and phytosociologial study has been done in the Natural Park Sierra de las Nieves, placed in Málaga (Andalusia, Spain). A total of 1.400 taxa have been recorded, fom which we have pointed out and commented 36, due to their biological value as endemisms, rare, protected or endemic species or new records in the studied area. One new taxonomical combination is proposed: Ulex baeticus subsp. bourgaeanus. A total of 78 associations and communities have been recorded. New sintaxa are described: one alliance (Pino pinastri-Juniperion phoeniceae), 12 associations, 9 subassociations and one new combination. The 6 climactic series described with their main tree species, soil and bioclimatic range are the following: two series of Quercus suber (termo-mesomediterranean on schists), one of Quercus rotundifolia (mesomediterranean on limestones), one of Quercus pyrenaica (mcsomediterranean on schists), one of Quercus alpestris (supramediterranean on limestones) and one of Juniperus sabina (oromediterranean on limestones). The 5 edaphoxeric series described with their main tree species, soil and bioclimatic range are the following: two series of Abies pinsapo (meso-supramediterranean on perdotite rocks and dolomite), two series of Juniperus phoenicea (termo-meso-supramediterranean on marble, dolomite and limestones) and one of Pious pinaster (termo-mesomediterranean on peridotite rocks). The 5 riverine edaphoseries described with their main tree species, soil and water-level range are the following: one of Fraxinus angustifolia (summer-droughted rivers on limestones), two of Salix pedicellata (summer-droughted rivers on peridotite rocks, schists and limestones) and two of Nerium oleander (seasonal streams, on peridotite rocks, schists and limestones). Finally, the complete sintaxonomic scheme, with new sintaxa, combinations, hierarchycity and comments on the associations and communities is given
Keywords: Andalusia; Flora; Málaga; series; Serranía de Ronda; Spain; Vegetation

Deriving indicators of soil degradation from soil aggregation studies in southeastern Spain and southern France - Cammeraat, L. H.; Imeson, A. C. (Geomorphology, 1998)
Soil degradation is perceived as a major threat in the Mediterranean region due to changes in land-use and possible future climate change. Soil aggregation parameters are used here to demonstrate their potential as a key-indicator for land degradation studies. The monitoring of these indicators offers a means of establishing the vulnerability and resilience of geo-ecosystems. Soil aggregation stability and distribution were studied on soils with an open shrubby vegetation cover, from several places in southeastern Spain and southern France, by applying drop tests and determining aggregate size distributions. Aspect and vegetation cover were incorporated in the soil sampling. Several indices were derived from these analyses to indicate the degree of soil aggregation. This was done by referencing to a base level of aggregation bare soil aggregation . It was found that soil aggregates were more stable and were often coarser under vegetation, when compared to . their immediate surrounding bare areas. A similar, slightly less clear effect was noted on N-facing exposed slopes when compared to S-facing exposed slopes. Long-term changes were found by studying cultivated land, abandoned fields and land covered by semi-natural vegetation, on comparable substrate and comparable land units. It is clear that soil aggregation and aggregate stability increases with time years . It is argued that soil aggregation indices can be used as a key-indicator for . degradation processes at a fine scale with implications for runoff and sediment generating processes at the hillslope scale
Keywords: degradation; Soil; Vegetation

Deriving indicators of soil degradation from soil aggregation studies in southeastern Spain and southern France - Cammeraat, L H; Imeson, A C (Geomorphology, 1998)
Soil degradation is perceived as a major threat in the Mediterranean region due to changes in land-use and possible future climate change. Soil aggregation parameters are used here to demonstrate their potential as a key-indicator for land degradation studies. The monitoring of these indicators offers a means of establishing the vulnerability and resilience of geo-ecosystems. Soil aggregation stability and distribution were studied on soils with an open shrubby vegetation cover, from several places in southeastern Spain and southern France, by applying drop tests and determining aggregate size distributions. Aspect and vegetation cover were incorporated in the soil sampling. Several indices were derived from these analyses to indicate the degree of soil aggregation. This was done by referencing to a base level of aggregation bare soil aggregation . It was found that soil aggregates were more stable and were often coarser under vegetation, when compared to . their immediate surrounding bare areas. A similar, slightly less clear effect was noted on N-facing exposed slopes when compared to S-facing exposed slopes. Long-term changes were found by studying cultivated land, abandoned fields and land covered by semi-natural vegetation, on comparable substrate and comparable land units. It is clear that soil aggregation and aggregate stability increases with time years . It is argued that soil aggregation indices can be used as a key-indicator for . degradation processes at a fine scale with implications for runoff and sediment generating processes at the hillslope scale
Keywords: degradation; Soil; Vegetation

Soil aggregate stability under different Mediterranean vegetation types - Cerdà, A. (Catena, 1998)
The influence of vegetation type on soil erodibility was studied by means of aggregate stability measurements using the Modified Emerson Water Dispersion Test MEWDT , water-drop impacts . . . CND and TDI and Ultrasonic Disruption UD methods on soils from north-facing slopes of the mountain range of La Serra Grossa in the eastern Iberian Peninsula. Soils with similar characteristics but covered by the main plant species at the study area were selected. Quercus ilex woodland showed the most resistant soil aggregates followed by Q. coccifera and Pistacea lentiscus scrubland, Brachypodium retusum grassland and Pinus halepensis woodland. Aggregates developed beneath dwarf shrubs like Rosmarinus officinalis, Thymus Íulgaris, Ulex parÍiflorus and Anthyllis cystisoides were least resistant. The different methods and tests applied are useful to study the soil aggregate stability. The MEWDT and TDI tests showed only minor differences between samples due to the high aggregate resistance and the low energy applied by these tests. CND and UD tests are considered to be more suitable for resistant Mediterranean soil developed on limestone due to the greater energy applied. Aggregates tested from an initially moist pF1 condition were always more stable than air dried aggregates. Rangeland management . after disturbances by fire, agriculture or grazing, etc. should try to establish natural woodland Q. ilex. in order to get the most stable soil. Alternative vegetation cover to the climax vegetation that give high aggregate stability are Q. coccifera and P. lentiscus scrublands. Immediately after disturbance, B. retusum grassland seems to be the best option for soil protection.
Keywords: Aggregate stability; Laboratory test; Mediterranean; Vegetation

Soil aggregate stability under different Mediterranean vegetation types - Cerdá, A (Catena, 1998)
The influence of vegetation type on soil erodibility was studied by means of aggregate stability measurements using the Modified Emerson Water Dispersion Test MEWDT , water-drop impacts . . . CND and TDI and Ultrasonic Disruption UD methods on soils from north-facing slopes of the mountain range of La Serra Grossa in the eastern Iberian Peninsula. Soils with similar characteristics but covered by the main plant species at the study area were selected. Quercus ilex woodland showed the most resistant soil aggregates followed by Q. coccifera and Pistacea lentiscus scrubland, Brachypodium retusum grassland and Pinus halepensis woodland. Aggregates developed beneath dwarf shrubs like Rosmarinus officinalis, Thymus Íulgaris, Ulex parÍiflorus and Anthyllis cystisoides were least resistant. The different methods and tests applied are useful to study the soil aggregate stability. The MEWDT and TDI tests showed only minor differences between samples due to the high aggregate resistance and the low energy applied by these tests. CND and UD tests are considered to be more suitable for resistant Mediterranean soil developed on limestone due to the greater energy applied. Aggregates tested from an initially moist pF1 condition were always more stable than air dried aggregates. Rangeland management . after disturbances by fire, agriculture or grazing, etc. should try to establish natural woodland Q. ilex. in order to get the most stable soil. Alternative vegetation cover to the climax vegetation that give high aggregate stability are Q. coccifera and P. lentiscus scrublands. Immediately after disturbance, B. retusum grassland seems to be the best option for soil protection.
Keywords: Aggregate stability; Laboratory test; Mediterranean; Vegetation

An overview of the Castelporziano experiments - Seufert, G; Bartzis, J; Bomboi, T; Ciccioli, P; Cieslik, S; Dlugi, R; Foster, P; Hewitt, C N; Kesselmeier, J; Kotzias, D; Lenz, R; Manes, F; et al. (Atmospheric Environment, 1997)
This paper reviews the major outcomes of the measuring campaigns performed at the Castelporziano nature preserve near Rome, Italy, by 14 European laboratories as part of the BEMA (Biogenic Emissions in the Mediterranean Area)-project. Six campaigns of 1–4 weeks duration were carried out in different seasons of the years 1993–1994 at semi-continuously running test plots in the nature reserve, representing common Mediterranean vegetation types. The aim was to characterise, at the different test plots, the atmospheric chemical and meteorological situations, the plant biomass and physiology, the type, amount and controls of emissions from different plants by means of branch enclosures, and the BVOC emission fluxes from different ecosystems, by scaling up enclosure data from individual sources, and by measuring fluxes directly by use of micrometeorological methods. An important focus during the initial phase of the five year BEMA-project was the harmonisation and improvement of the analytical, physiological and micrometeorological methods used, and the development and testing of new methods for measuring BVOC fluxes.
Keywords: air chemistry; Biogenic emission; ecophysiology; Mediterranean area; micrometeorology; Vegetation

Scaling up the biogenic emissions from test sites at Castelporziano - Lenz, Roman; Selige, Thomas; Seufert, Günther (Atmospheric Environment, 1997)
On the basis of measurements of emission rates, Leaf Area Indices (LAI) and biometric data for 17 species and 15 land-cover types, a first scaling up of biogenic emissions for the Castelporziano test site is elaborated It includes the application of different procedures for scaling up, by combining parameters (e.g. LAI, biomass, vegetation coverage, canopy layering, insolation) with emission rates and algorithms in a spatial model. This approach consists of the following steps: (i) elaboration of a pseudo-3D Geographical Information System (GIS) for the test site St. Quercio, and 2D GIS for pseudosteppe, dunes and whole Castelporziano, (ii) calculations of relations between diameter at breast height (dbh), biomass and LA1 from literature and our own data, at St. Quercio, (iii) application of an insolation model in the stands for one to two canop:y layers and surfaces in a l/4 square meter resolution, at St. Quercio; (iv) classified incoming light is driving the emissions of monoterpenes from Stone pine and Holm oak at the test site St. Quercio. For temperature we do not scale up and apply any algorithm to date, but we can show some preliminary surface temperature data from remote sensing activities, possibly to be used during further campaigns. Calculations of total emission fluxes are intercompared for the test site St. Quercio according to the different calculation rules, e.g. the relevancy of spatial effects. The differences between the biomass-based fluxes and the LAI-based fluxes are in the range of 5-30%. The application of the GIS model for light interception for the pine canopy, and for’two canopy layers for Holm oak, is shown for the open stands at St. Quercio. The resulting biogenic emissions are in good accordance with the ones calculated only via biomass or LAI, and the lower parts of a crown seem to be negligible in terms of biogenic emissions.
Keywords: Biogenic emissions; geographical information system; GIS; Land Cover; light interception; scaling up; spatial modelling; Vegetation